Cellular Delivery of Noncovalently-Associated Macromolecules by Cell- Penetrating Peptides - Chang, Microsugar; Huang, Yue-Wern; S. Aronstam, Robert; Lee, Han-Jung (Current Pharmaceutical Biotechnology, 2014)
Cellular and nuclear delivery of biomolecules is limited by low membrane permeability. Cell-penetrating peptides (CPPs) can be covalently linked to cargos to improve cellular internalization. Our work indicates that arginine-rich CPPs are also able to interact with a variety of cargos, including DNA, RNA, proteins and nanomaterials, in a noncovalent manner and subsequently effect their delivery into cells. The advantages of noncovalent attachment in CPP-mediated transduction are multiple: ease of use, ease of production, and versatility with respect to both cargo composition and functional delivery (i.e., the cargo is not chemically modified). We have extended this approach to achieve simultaneous transduction of covalently and noncovalently associated complexes, opening a new method for delivering multiple types of cargos, including proteins, fluorescent nanomaterials, nucleic acid and others. These novel variations of CPP-mediated transport should be of broad utility in the transport of genes, small interfering RNAs, proteins and nanoparticles in biomedical research and therapeutic intervention.
Keywords: cell-penetrating peptide